To build a city in Africa : the urban hub of Diamniadio in Senegal, a new town in the Dakar metropolitan region facing the challenge of sustainable urban planning - (:unkn) unknown (My University, 2023)
The "new town" is no longer a recipe for success in many Western countries, especially in urban policies. But in the countries of the global South, especially China and many African countries facing multiple urban challenges, emblematic projects heralded as "new cities" are seeing the light of day. Today, in light of new challenges and specific geographical contexts, the term deserves to be revisited. This research focuses on new city projects in Africa in general and the case of Diamniadio in Senegal in particular. The interest shown by governments in the new town option is part of a dual context. On the one hand, since the 2000s, most African countries have experienced a bifurcation marked by the return of strong economic growth and a diversified urban field invested by large private groups and non-governmental organizations (NGOs). At the global scale, urban thinking has evolved from "sustainable development" to the "sustainable city". In Dakar, Senegal, the planning approach has been to implement major infrastructure projects on the outskirts of the city, with the aim of reducing the concentration of activities and populations and redistributing them to new urban centers. However, the emerging urban reality is still unknown. This is the purpose of this research. Using the example of the Diamniadio urban hub in the Dakar metropolitan region, it aims to understand the process of building a new town in the context of metropolitanization and the sustainable city.
Keywords: African Research